Use of the geographic information system GIS/INPE for environmental characterization of the microbasin of Taquara creek watershed, DF, Brazil - Sano, Edson Eyji; Meirelles, Maria Lúcia; Assad, Eduardo Delgado; Moreira, Lucimar; Macedo, Jamil; Resck, Dimas Vital Siqueira (Pesquisa Agropecuaria Brasileira, 1991)
This study aimed to characterize land feature of the microbasin of Taquara Creek Watershed, (DF), at a scale of 1:20,000, through the use of the SGI/INPE geocoded information system. The study area corresponds to the pilot watershed for the Federal District in Brazil on the Ministry of Agriculture's National Program for Small Watersheds As an aid to rational land use planning in the basin through the use of soil and water conservation management practices, this characterization was obtained through the digital overlay of 224 combinations of soil classes, slope classes, and current land use classes. The SGI/INPE geocoded information system proved to be an important tool, principally for the facility for automatic overlaying and for the integration of data involving complex operations, resulting in increased accuracy of the final product and time saved in relation to traditional analysis methods.
Keywords: land use; water conservation management; digital overlay